The Welfare of Pigs - Marchant-Forde, Jeremy N. (Animal Welfare ;, 2009)
The domestic pig is perceived as an animal with intelligence and character and yet, in the industrialized world, the majority of people have had little or no contact with them. Pigs are subject to a wide range of environments from the tropics to the sub-arctic, ranging from small-scale, extensive systems to large-scale intensive systems. They may spend their whole life on one farm or may be subject to long-distance transport multiple times. Not surprisingly, many aspects of their life experiences can impact their welfare. This book brings together a team of leading pig welfare research scientists to review the natural history of the pig, the welfare of pigs at different stages of life and to indicate what the future holds in terms of pig welfare. The text is aimed at researchers and teachers working in veterinary and animal science together with those working in the pig industry and for governmental and non-governmental animal welfare organizations.